2022
DOI: 10.2174/18749445-v15-e2201120
|View full text |Cite
|
Sign up to set email alerts
|

Student Nurses Attitudes Towards Using Social Media to Raise the Awareness of their Community about the COVID-19 Pandemic in Jordan

Abstract: Aims: The current study investigates the student nurses' attitudes and opinions towards their health promotion role during the COVID-19 pandemic using social media. Background: Social media and networking have become the most secure modes of communication among health care providers and their clients during the COVID-19 pandemic all over the world. However, it is the primary means of disseminating health information about disease prevention and control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Similarly, Karasneh et al (13) found that social media networking sites and the internet were the primary means for sharing COVID-19-related information. Furthermore, an international study has been undertaken on health professionals' attitudes toward using social media for accessing health information (14)(15)(16)(17)(18). Jordanian evidence revealed that nursing students were enthusiastic about using social media to access COVID-19 information (15,19).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Karasneh et al (13) found that social media networking sites and the internet were the primary means for sharing COVID-19-related information. Furthermore, an international study has been undertaken on health professionals' attitudes toward using social media for accessing health information (14)(15)(16)(17)(18). Jordanian evidence revealed that nursing students were enthusiastic about using social media to access COVID-19 information (15,19).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, an international study has been undertaken on health professionals' attitudes toward using social media for accessing health information (14)(15)(16)(17)(18). Jordanian evidence revealed that nursing students were enthusiastic about using social media to access COVID-19 information (15,19). Similar studies identified that health professionals' use of social media platforms had been considered an efficient instrument for education, exchange, and communication in the COVID-19-related information (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation